Membangun Kepercayaan Diri Santri melalui Pelatihan Pidato di TPQ As-Shidiq Dukuh Mirah Desa Nambangrejo Sukorejo Ponorogo - Fuaddah, Dannur; Wahyuni, Fitri; Sholeh, Moh. (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Self-Confidence is an important Component in the psychological development of children, including students at the Al-Quran Education Park ( TPQ).The Al-Quran Education Park (TPQ) offers speech training, which is crucial for boosting students' self-esteem. In addition to instructing students in public reading skills, this program serves as a vehicle for da'wah, enhancing their comprehension of religion. This research aims to examine the effect of speech training on increasing the self-confidence of TPQ As-Shidiq students.Self-development theory (Carl Rogers), Rogers emphasized the importance of a supportive environment for individual growth. In speech research, it is important to create a safe environment: make students feel comfortable speaking first and a Person-Centered approach: appreciate every student's efforts, so that they feel supported and accepted. The results of this training show that students are not only able to communicate better, but they can also participate more actively in religious activities in society. This research uses a qualitative descriptive method, through a case study approach on Santri TPQ As-Shidiq in Dukuh Mirah, Nambangrejo Village, Sukorejo, Ponorogo.